2021
DOI: 10.1177/0022167821993243
|View full text |Cite
|
Sign up to set email alerts
|

From Climate Anxiety to Climate Action: An Existential Perspective on Climate Change Concerns Within Psychotherapy

Abstract: With the growing body of knowledge climate change stands out as one of the most important contemporary problems. The Intergovernmental Panel on Climate Change confirms the urgent necessity to reduce greenhouse gases emission, as the window to address the problem is becoming narrow. Rising temperatures and bushfires, melting glaciers and droughts make the acceleration of climate change evident, and citizens around the globe are increasingly worried about the magnitude of the problem. In this article, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 5 publications
0
48
0
1
Order By: Relevance
“…-Earlier research about taxonomies of environmentally relevant emotions (Landmann, 2020). -Studies which have discussed some climate emotions as part of their focus on climate anxiety and/or eco-anxiety (Kelly, 2017;Hickman, 2020;Pihkala, 2020a,b;Verplanken et al, 2020;Budziszewska and Jonsson, 2021;Marczak et al, 2021;Stanley et al, 2021) and Wettergren, 2017;du Bray et al, 2019), and climate hope (e.g., Ojala, 2012bOjala, , 2017Bury et al, 2020). Terminology about these emotions varies, and often the formulations of "ecological X" or "eco-X, " with X referring to a certain emotion, are used.…”
Section: Climate Emotions In Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…-Earlier research about taxonomies of environmentally relevant emotions (Landmann, 2020). -Studies which have discussed some climate emotions as part of their focus on climate anxiety and/or eco-anxiety (Kelly, 2017;Hickman, 2020;Pihkala, 2020a,b;Verplanken et al, 2020;Budziszewska and Jonsson, 2021;Marczak et al, 2021;Stanley et al, 2021) and Wettergren, 2017;du Bray et al, 2019), and climate hope (e.g., Ojala, 2012bOjala, , 2017Bury et al, 2020). Terminology about these emotions varies, and often the formulations of "ecological X" or "eco-X, " with X referring to a certain emotion, are used.…”
Section: Climate Emotions In Previous Researchmentioning
confidence: 99%
“…As seen above in Table 1, feelings of hopelessness have been recognized in several studies in relation to the climate crisis and the global ecological crisis. Therapists have observed feelings of meaninglessness in some of their clients who feel climate anxiety, testifying to the manifestations of eco-anxiety as deep existential anxiety (Lewis et al, 2020;Budziszewska and Jonsson, 2021). Anxiety of meaninglessness, a classical category in theories of existential anxiety (Yalom, 1980), seems to be a difficult and quite common form of eco-anxiety (Pihkala, 2020a).…”
Section: Strong Anxiety Depression Despairmentioning
confidence: 99%
“…Although relatively few CCE research studies have documented action-focused pedagogies and their impacts on young learners [5], findings of the present study take on expanded significance in the context of increasingly apparent mental health impacts linked with climate change [29], including among young people [1,2]. An unexpected finding in this study was that, in addition to its psychological benefits, children's climate action may have conferred additional mental and physical health benefits through children's increased outdoor activity.…”
Section: Children's Climate Change Action: Micro-level Benefitsmentioning
confidence: 89%
“…For example, a recent study found that children showed greater climate message engagement (vs. avoidance) when the problem was attributed to internal causes (vs. forces external to the self) [28]. Moreover, a growing body of research suggests that when people are given opportunities to act individually and collaboratively to address climate change, they are able to gain a sense of constructive hope and agency that it lies within their capabilities to take meaningful action to address the problem [7,25,[29][30][31]. As such, rather than instilling a sense of guilt or other psychological burdens, action opportunities in CCE contexts may be a critical element in efforts to create empowering learning environments that support children's positive and sustained engagement.…”
Section: Children's Climate Change Actionmentioning
confidence: 99%
“…The first is that learners often struggle to reconcile global-scale phenomena with their individual experiences (Van der Linden, 2015). The quantity of information, as well as the negativity of environmental issues, means that audiences can become anxious, overwhelmed or desensitised and subsequently disengage (Budziszewska and Jonsson, 2021; Clayton, 2020). The complex nature of earth and environmental sciences make them difficult to teach in an engaging and comprehensible way.…”
Section: Introductionmentioning
confidence: 99%